Mapping and assessing ecosystem service supply–demand to identify critical areas: A case study of a waterside area in Shanghai metropolitan area - Ni, Yuchun; Wei, Jiaxing; Wu, Tao; Guo, Min; Han, Qiyao; Zhang, Mingjuan (Frontiers in Earth Science, 2022)
In the past decades, rapid urbanization in China has dramatically transformed natural spaces into construction land, leading to serious degradation and supply–demand imbalance of ecosystem services (ESs). The identification of critical areas and ecological security patterns is crucial for balancing ESs and improving human well-being in rapidly urbanized regions. The purpose of this study was to establish a comprehensive assessment framework of ES supply–demand including provisioning, regulating, supporting, and cultural services, so as to provide theoretical support for the identification and refined management of regional critical areas. Taking a typical waterside area in Shanghai metropolitan area as an example, based on multi-source data and ES quantitative models, we used ecological supply–demand ratio and bivariate local indicators of spatial association to quantify the relationship and matching patterns of ES supply–demand, then explored the identification, protection, and restoration of ecologically critical areas at the regional scale. The results showed that: 1) the ES supply–demand relationship in the study area was quantitatively determined. The ecological supply–demand ratio was as follows: regulating > provisioning > supporting > cultural, in which the supply of supporting and cultural services was less than the demand, and the problem of the supply–demand mismatch is prominent; 2) we have identified 41 supply critical areas that require priority protection, with a total area of 206.79 km2 accounting for 9.65% of the total study area, showing a spatial pattern of more in the northwest and less in the southeast; 3) a total of 11 demand critical areas that need ecological restoration were identified, accounting for 31.43% of the 35 administrative towns in the study area, which are mainly distributed around three urban centers and a high-tech zone. The study is of great significance for the construction of regional ecological security patterns and rational ES allocation, and can provide a scientific framework for the ecological protection and restoration of critical areas around metropolises in developing countries.